Precision Agriculture Technologies for Smallholder Farming Systems in Developing Countries: A Scoping Review of Opportunities, Limitations and Future Directions - MBACHIRIN, Daniel N.; ABEL, David E.; OMALE, Paul A. (FUDMA Journal of Engineering and Technology, 2026)
Precision agriculture (PA) has emerged as a transformative approach for improving productivity, resource use efficiency, and environmental sustainability in modern farming systems. However, its adoption in developing countries where smallholder farmers dominate agricultural production remains limited and uneven. This scoping review critically examines the opportunities, constraints, and future prospects of precision agriculture in smallholder-dominated systems across Sub-Saharan Africa, South Asia, and Latin America. The paper synthesizes current evidence on the benefits of precision technologies, including remote sensing, Internet of Things (IoT) devices, artificial intelligence (AI)-driven advisory platforms, and unmanned aerial vehicles (UAVs), highlighting their potential to enhance yield optimization, reduce input waste, improve water management, and strengthen climate resilience. Despite these advantages, structural barriers such as high capital costs, weak digital infrastructure, fragmented landholdings, low technical literacy, inadequate extension services, and policy gaps significantly constrain adoption. Case studies from developing regions reveal that successful implementation often depends on institutional support, cooperative models, mobile-based platforms, and public–private partnerships. The review argues that transitioning from technology-centric approaches to system-oriented innovation frameworks is essential for inclusive and scalable implementation. Future directions should prioritize low-cost innovations, mobile-integrated precision tools, and shared service models for advanced technologies, AI-powered decision-support systems, and enabling policy environment. Ultimately, precision agriculture can contribute meaningfully to sustainable intensification and global food security, but its impact in developing countries will depend on context-specific design, equitable access mechanisms, and coordinated institutional support.
Keywords: Precision agriculture, Digital agriculture, Smallholder farming, Input optimization, Sustainable intensification, Technology adoption.